Karakteristik Fisik dan Fungsional Tepung Labu Kuning LA3 Desa Tegalrejo, Kecamatan Tegalsari, Kabupaten Banyuwangi - Fauzi, Mukhammad; Herlina, Herlina; Sholeha, Indri M (Universitas Pattimura, 2023)
LA3 pumpkins are one of the pumpkin variants cultivated in Indonesia, especially in Tegalrejo, Tegalsari Districts, Banyuwangi Regency. LA3 pumpkin production is relatively high, however, its utilization is still low. The waste of LA3 pumpkin pulp is relatively high because farmers only take its seeds. In the origin, during harvest time, LA3 pumpkins are harvested and stored for two weeks before taking its seeds, while the whole pumpkin can be stored for up to three months. After two weeks the pumpkin will be cut open and take their seeds, this action will reduce the pumpkin’s shelf life. However, increasing the LA3 pumpkin’s shelf life can be done by milling the pulp into flour. This study aimed to determine the physical and functional characteristics of LA3 pumpkin flour from the pumpkin that has been stored. In this study, the harvested LA3 pumpkin was stored for both 2 weeks and 2 months, which was repeated 9 times, and then the pumpkin was milled into flour. The data obtained were analyzed by t-test. The values ​​for brightness, viscosity, water holding capacity, and swelling capacity of pumpkin flour stored for 2 weeks had higher values ​​than pumpkin flour stored for 2 months. In contrast, the bulk density, bulk angle, oil binding capacity, and solubility, of flour from pumpkin stored for 2 months had higher values.